Discovery of Enhydrictis (Mustelidae, Carnivora, Mammalia) cranium in Puwan, Dalian, Northeast China demonstrates repeated intracontinental migration during the Pleistocene. (20th April 2019) - Jiangzuo, Qigao; Liu, Jinyuan; Jin, Changzhu; Song, Yayun; Liu, Sizhao; Lü, Sheng; Wang, Yuan; Liu, Jinyi
Abstract: The tribe Lyncodontini (Mammalia, Carnivora, Mustelidae) was widely distributed in Eurasia during the Plio-Pleistocene. In East Asia, only Eirictis and Oriensictis are known so far. Herein, we describe a new complete cranium of Lyncodontini from Layer 2 of Jinyuan cave of Luotuo Hill, Puwan area of Dalian, Liaoning Province in Northeast China and undertake detailed comparisons with related taxa. The specimen is similar to Oriensictis, especially Oriensictis melina in Locality 1 of Zhoukoudian in tooth morphology and represents the same species of the latter, but the cranial characters are strikingly similar to those of Enhydrictis galictoides from Sardinia. We therefore relegate Oriensictis to a subgenus of Enhydrictis as East Asian members of the clade in the Middle Pleistocene, whereas the subgenus Enhydrictis is endemic to Sardinia. The craniodental characters of E. melina are more derived than those of E. galictoides in many aspects, so it is unlikely to be a direct ancestor to E. galictoides . The Early Pleistocene Martellictis ardea from Saint Vallier probably represents the ancestor group of this genus. This clade immigrated along the Paratethys during the Late Villafranchian. Part of this metapopulation probably dispersed into East Asia during the late Early Pleistocene or early Middle Pleistocene along with other carnivores (e.g. Xenocyon sp. and Panthera youngi ) during interglacial period, whereas others dispersed back to Europe during the Middle Pleistocene, as represented by the Sardinia population. The E. melina from Layer 2 of Luotuo Hill is morphologically more derived than the Middle Pleistocene E. nipponica from Japan, thus the age of Layer 2 is possibly not older than Middle Pleistocene.